Polyphyly of the Zaprionus genus group (Diptera: Drosophilidae) - Yassin, Amir; Da Lage, Jean-Luc; David, Jean R.; Kondo, Masanori; Madi-Ravazzi, Lilian [UNESP]; Prigent, Stephane R.; Toda, Masanori J. (Academic Press Inc. Elsevier B.V., 2010)
The Zapnionus genus group comprises three drosophilid genera (Zaprionus, Phorticella and Samoaia) that are thought to be related to the Drosophila immigrans species group. We revised the phylogenetic relationships among the three genera and their placement within the subfamily Drosophilinae using one mitochondrial (COII) and one nuclear (Amyrel) gene. The Bayesian tree inferred from concatenated amino acid sequences of the two genes strongly suggests the polyphyly of the Zaprionus genus group and of each of the genera Zaprionus and Phorticella. Paraphyly of the D. immigrans species group was also shown here; the quadrilineata subgroup formed the sister clade to the genus Samoaia. These results suggest the necessity of taxonomic revisions for some relevant genera and species groups included within the genus Drosophila. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Genus concept; Drosophila; Notal pattern; Nomenclature